Is Metaphysics the only Discipline that Can Be Complete? The Completeness of Metaphysics in Kant and Wolff - Picas Prats, Bruna; Jakušić, Dino (Con-Textos Kantianos. International Journal of Philosophy, 2025)
The aim of this article is twofold. First, against Marcus Willaschek’s statement that Kant’s systematicity of metaphysics is shared with the other sciences, it examines Kant’s assertion that metaphysics is the only discipline capable of achieving completeness. Second, this article explores the continuity between Kant and Wolff regarding the inquiry about what criterion of completeness is suitable for metaphysics as a system. To this end, we address two central questions: what does it mean for metaphysics to be ‘complete’? Is there something special about the completeness of metaphysics that is not shared by other sciences? We will identify two kinds of completeness, which we refer to as ‘unconditioned completeness’ and ‘comprehensiveness’ and demonstrate the continuity in how Kant and Wolff understand these terms. Furthermore, we will demonstrate that both Kant and Wolff argue that unconditioned completeness is unique to metaphysics. Finally, we will discuss why, despite these similarities, Kant would still be dissatisfied with Wolff’s conception of metaphysical completeness.